Pengaruh Brand Awareness dan Kualitas Produk terhadap Loyalitas Pelanggan melalui Kepuasan Konsumen sebagai Variabel Intervening - Azzahra Ananda Pattilasa; Jojok Dwiridotjahtjono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Business development in Indonesia is experiencing intense competition in various sectors, one of which is the cosmetic industry in Indonesia, namely Pixy. One of the beauty products produced by Pixy is compact powder. This study aims to determine how much influence Brand Awareness and product quality have on Customer Loyalty to Pixy Compact Powder customers in Surabaya. The population in this study were 100 respondents who had purchased and used Pixy Compact Powder in the city of Surabaya. The research method is descriptive quantitative. The sampling technique used is purposive sampling technique with the criteria that Pixy Compact Powder consumers are domiciled in the city of Surabaya and are at least 17 years old. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the Brand Awareness (X1) and product quality (X2) variables simultaneously have a significant effect on Customer Loyalty (Y), the Brand Awareness (X1) variable partially has a positive and significant effect on Customer Loyalty (Y), and product quality (X2) partially positive and significant effect on Customer Loyalty (Y). Keywords: Brand Awareness, Quality product, Customer Loyalty